First-Time-Right Procurement: Substitution of the Paradox Purchasing Savings through First-Time-Right Procurement (FTRP) - Münch, Oliver (Springer, 2015)
Based on more than 10 years of practical experience in the field of supply chain management, Oliver Münch indicates that in favor of sustainability within the supply chain the paradox purchasing savings can and should be substituted with the approach of the First-Time-Right Procurement. This dissertation subjects the monetary measurement of purchasing savings to a critical examination and questions whether it still applies. It indicates that monetary purchasing savings exert a negative impact on sustainable company success. In order to achieve a long-term sustainable success, it is proposed that the monetary measurement of purchasing savings can be replaced by measuring process times within the procurement organization.